Percutaneous paravalvular leak closure: a single-centre experience of 54 cases. (4th February 2022) - Vertesaljai, M; Denes, M; Temesvari, A; Fontos, G; Andreka, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Clinically significant paravalvular leak (PVL) occurs in 5-10% of patients undergoing surgical aortic and 5-17% patients undergoing surgical mitral valve replacement and even more often after trancutaneous aortic valve implantation (TAVI). Surgical repair of a PVL is associated with a 30-day mortality of approximately 10%. Percutaneous closure of PVL (pPVLC) has emerged as an alternative to surgical repair. Aim: We retrospectively analysed the success rate and clinical outcomes of patients with significant PVL, who were turned down from re-do cardiac surgery, and treated with pPVLC at our tertiary referral centre. Methods: Patients who were admitted for pPVLC between 27th of September, 2009 and 21st of April, 2021 were enrolled into the study. 30-day and 1-year mortality rates were assessed. Technically successful pPVLC was defined as stable device position, and minimum 1 grade reduction in PVL severity. Results: pPVLC was performed in 54 cases (32 males, 22 females, mean age: 69.5 ± 10.9 yrs). The main indication for closure was heart failure (81%) and haemolysis (19%). The median time since valve surgery was 4.5 yrs (IQR: 0.9-15.2 yrs). Regarding the leaks, 70% (n = 38) were in mitral position (mechanical vale: 33 cases, bioprosthesis: 5 cases) and 30% (n = 16) in aortic position (mechanical valve: 12 cases, bioprosthesis: 2 cases, TAVI: 2 cases). A total of 53 leaks were identified in mitral position (one leak: 25 cases, two leaks: 11 cases, three leaks: 2 cases), and 25 leaks in aortic position (9 cases, 5 cases and two cases resp.). In mitral position 1 device was used in 73% of cases, 2 devices in 21%, and 3 devices in 6%. In aortic position: 62%, 19%, and 19 % resp. Techinal succes was achieved in 49 case (91%). The 30-day mortality was 8%, the 1-year mortality 21%. Conclusions: Patients with significant PVL represent an extreme or even prohibitive surgical risk cohort. In these high risk individuals percutaneous PVL offers a safe alternative to surgical PVL repair and appears particularly effective in patients presenting with heart failure or haemolysis.